Modulation of defect-mediated energy transfer from ZnO nanoparticles for the photocatalytic degradation of bilirubin - Bora, Tanujjal; Lakshman, Karthik Kunjali; Sarkar, Soumik; Makhal, Abhinandan; Sardar, Samim; Pal, Samir Kumar; Dutta, Joydeep (Beilstein Journal of Nanotechnology, 2013)
In recent years, nanotechnology has gained significant interest for applications in the medical field. In this regard, a utilization of the ZnO nanoparticles for the efficient degradation of bilirubin (BR) through photocatalysis was explored. BR is a water insoluble byproduct of the heme catabolism that can cause jaundice when its excretion is impaired. The photocatalytic degradation of BR activated by ZnO nanoparticles through a non-radiative energy transfer pathway can be influenced by the surface defect-states (mainly the oxygen vacancies) of the catalyst nanoparticles. These were modulated by applying a simple annealing in an oxygen-rich atmosphere. The mechanism of the energy transfer process between the ZnO nanoparticles and the BR molecules adsorbed at the surface was studied by using steady-state and picosecond-resolved fluorescence spectroscopy. A correlation of photocatalytic degradation and time-correlated single photon counting studies revealed that the defect-engineered ZnO nanoparticles that were obtained through post-annealing treatments led to an efficient decomposition of BR molecules that was enabled by Förster resonance energy transfer.
Keywords: bilirubin; Förster resonance energy transfer (FRET); neonatal jaundice; oxygen vacancy; photocatalysis; phototherapy; zinc oxide nanoparticles